An ESIPT-based mitochondria-targeted ratiometric and NIR-emitting fluorescent probe for hydrogen peroxide and its bioimaging in living cells. (November 2018) - Tang, Lijun; Tian, Mingyu; Chen, Haibo; Yan, Xiaomei; Zhong, Keli; Bian, Yanjiang
Abstract: A mitochondria-targetable ratiometric fluorescent probe, HBTPB, has been developed for the detection of H2 O2 with a near infrared (NIR) emission and a large Stokes shift (357 nm). Probe HBTPB displays high selectivity toward H2 O2 over other reactive oxygen/nitrogen species (ROS/RNS), biological thiols and anions. The detection limit of this probe is as low as 5.9 × 10 −7  M. The sensing process confirmed by NMR and mass spectral analysis shows that the addition of H2 O2 to the solution of HBTPB triggers an oxidative hydrolysis and a subsequent elimination reaction undergoes to release an ESIPT (excited-state intramolecular proton transfer) featured fluorescent dye. Probe HBTPB is cell permeable and has been applied to sense exogenous and endogenous H2 O2 in living A549 cells. Graphical abstract: An ESIPT-based mitochondria-targetable ratiometric and NIR-emitting fluorescent probe for the detection of H2 O2 has been developed. Image 1 Highlights: A new ESIPT-based NIR-emitting fluorescent probe HBTPB was synthesized. HBTPB exhibits high selectivity and sensitivity to H2 O2 in an aqueous solution. HBTPB responses to H2 O2 through ratiometric fluorescence changes with a large Stokes shift. HBTPB is mitochondria-targetable and applicable for H2 O2 detection in living cells.